2020
DOI: 10.1111/jcmm.16103
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids decreased Cx43 expression in osteonecrosis of femoral head: The effect on proliferation and osteogenic differentiation of rat BMSCs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…In this study, the rats with GC administration had almost invisible structural trabeculae and decreased BV and BMD in the subchondral bone. Further histological study showed that the necrotic area was occupied by non-structural chondrocytes, which is consistent with the findings of several studies, [22,23] but differs from others that showed large numbers of empty lacunae filling the bone trabeculae, as well as disordered, sparser, or destroyed bone trabeculae [24,25] . Since Morini et al [26] observed that subchondral trabeculae originated from the ossification of the diaphysis and do not start before the third month, we speculate that the differences in the histological studies were likely due to different treatments and different sampling times.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the rats with GC administration had almost invisible structural trabeculae and decreased BV and BMD in the subchondral bone. Further histological study showed that the necrotic area was occupied by non-structural chondrocytes, which is consistent with the findings of several studies, [22,23] but differs from others that showed large numbers of empty lacunae filling the bone trabeculae, as well as disordered, sparser, or destroyed bone trabeculae [24,25] . Since Morini et al [26] observed that subchondral trabeculae originated from the ossification of the diaphysis and do not start before the third month, we speculate that the differences in the histological studies were likely due to different treatments and different sampling times.…”
Section: Discussionsupporting
confidence: 89%
“…Further histological study showed that the necrotic area was occupied by non-structural chondrocytes, which is consistent with the findings of several studies, [ 22 , 23 ] but differs from others that showed large numbers of empty lacunae filling the bone trabeculae, as well as disordered, sparser, or destroyed bone trabeculae. [ 24 , 25 ] Since Morini et al [ 26 ] observed that subchondral trabeculae originated from the ossification of the diaphysis and do not start before the third month, we speculate that the differences in the histological studies were likely due to different treatments and different sampling times. In addition, the rats that received GC treatment accompanied by lithium presented with fewer pathological changes and relatively normal trabecular structures, together with better trabecular parameters, indicating the protective effect of lithium against bone loss in femoral heads induced by GC.…”
Section: Discussionmentioning
confidence: 96%
“…Glucocorticoid-induced ONFH is a common metabolic disorder of bone, which is often caused by the serious side effects of long-term use or overdose of glucocorticoid drugs. There have been proposed several potential hypotheses to account for the glucocorticoid-induced ONFH initiation and progression, including the differentiation imbalance of BMSCs, apoptosis of osteocytes and osteoblasts, abnormal intraosseous pressure, increased oxidative stress, etc., 23 , 24 , 25 , 26 although until now, the specific underlying mechanism involved in ONFH pathogenesis and development remains unclear, limiting the diagnosis and treatment strategies for ONFH. BMSCs are a subset of adult stem cells derived from mesodermal cell lineages, and they have strong potential in multi-lineage differentiation and self-renewal capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The modified lipopolysaccharide and hormone modeling method was used to establish a model of hormone-induced osteonecrosis in rabbits ( Zhao et al, 2020 ). Firstly, the rabbits were injected with 10 μg/kg of lipopolysaccharide (LPS; Sigma) intravenously.…”
Section: Methodsmentioning
confidence: 99%